Burned-N-Turned: feeding the fracking boom. Issue 4 (30th March 2019) - Anderson, Beauvais R.; Anderson, Joe; Williams, Susan K.
Abstract : Theoretical basis: The discussion questions relating to the case focus students' attention on breaking away from the intuitive/emotional "boom mentality" driving their business decision and ask them to focus more on analytical decision criteria to support their "go" or "no-go" decisions. Research methodology: The authors interviewed one of the partners of Burned-N-Turned several times and read the partners' brief business plan for the food trailer. Case overview/synopsis: Partners are wrapped up in the "boom mentality" in the Bakken oil fields in 2011 and jump into their decision to open a food trailer restaurant to serve the oil field workers and others. But have they omitted important considerations for their business decision? Complexity academic level: The study is appropriate for undergrad strategic management courses. The authors have tested the compact case in three sections of capstone senior-level strategic management courses.